2012
DOI: 10.1016/j.jacc.2012.08.107
|View full text |Cite
|
Sign up to set email alerts
|

TCT-92 Does mitral regurgitation impact the outcome of TAVI procedures? Insights from the FRANCE2 Registry

Abstract: complication in Balloon-expendable (BE) and Self-expendable (SE) TAVI procedures remain unclear. Methods: 2,769 patients consecutive with a successful procedure and a predischarge transthoracic echocardiography (TTE) were enrolled in 33 centers. Mean follow-up was 302Ϯ164 days. Results: Mean age was 83Ϯ7 years; 49% were female and logistic EuroSCORE was 21.5Ϯ13.8. BE and SE devices was implanted in 67.6% (nϭ1872) and 32.4% (nϭ897), respectively. Approaches were femoral (75.4%) or non femoral: subclavian (5.6%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The final analysis was performed on a total of 8 studies comprising 8927 patients, meeting all inclusion and no exclusion criteria. The studies included 7 non-randomized registries [9][10][11][12]14,18,19 and 1 study reporting combined outcomes from the randomized controlled PARTNER trials (Cohorts A and B) 8 Study outcomes are summarized in Table 3. The presence of moderate-severe MR at baseline was associated with increased all-cause mortality at 30-days (RR 1.35, 95% CI 1.14-1.59, p = 0.0003, I 2 = 0%, chi 2 = 6.02) and 1 year (RR 1.24, 95% CI 1.13-1.37, p < 0.0001, I 2 = 0%, chi 2 = 5.15) ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The final analysis was performed on a total of 8 studies comprising 8927 patients, meeting all inclusion and no exclusion criteria. The studies included 7 non-randomized registries [9][10][11][12]14,18,19 and 1 study reporting combined outcomes from the randomized controlled PARTNER trials (Cohorts A and B) 8 Study outcomes are summarized in Table 3. The presence of moderate-severe MR at baseline was associated with increased all-cause mortality at 30-days (RR 1.35, 95% CI 1.14-1.59, p = 0.0003, I 2 = 0%, chi 2 = 6.02) and 1 year (RR 1.24, 95% CI 1.13-1.37, p < 0.0001, I 2 = 0%, chi 2 = 5.15) ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of moderate-severe MR was associated with increased 30-day rehospitalization rates (RR 1.75, 95% CI 1.02-2.99, p = 0.04, I 2 = 0%, chi 2 = 0.60); the Mortality at one year was analyzed according to the type of transcatheter heart valve implanted. One study used the CoreValve device 10 , 4 studies used the Edwards valve 8,9,12,18 and 3 studies used both valve types 11,14,19 . Consistent with the increased 1-year mortality overall (as reported previously), both CoreValve (RR 1.42, 95% CI 1.08-1.86, p = 0.01, heterogeneity not applicable) and Edwards valve studies (RR 1.21, 95% CI 1.02-1.42, p = 0.02, I 2 = 14%, chi 2 = 3.48) had a statistically significant increase in 1 year mortality with moderate-severe MR ( Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…when patients undergoing taVr are taken into account, the situation in similar, with some study showing an increased mortality associated with significant MR [11][12][13][14][15][16][17] and others in which this association did not reach the statistical significance [18][19][20][21] . another meta-analysis, recently published, showed that patients with moderate-to-severe Mr undergoing taVr have a significantly increased mortality compared to no/mild MR at 30 days(es -0.18; 95% CI: -0.31 to -0.04), 1 year (es -0.22; 95% CI -0.36 to -0.08) and 2 years(es -0.15; CI: -0.27 to -0.02)after taVr 22 .…”
Section: Impact Of Significant Mr On Mortality In Patients Undergoingmentioning
confidence: 75%